Patients with multiple myeloma have excellent long‐term outcomes after recovery from dialysis‐dependent acute kidney injury. (16th September 2015) - Yadav, Punit; Hutchison, Colin A.; Basnayake, Kolitha; Stringer, Stephanie; Jesky, Mark; Fifer, Lesley; Snell, Kym; Pinney, Jennifer; Drayson, Mark T.; Cook, Mark; Cockwell, Paul
Abstract: Objectives: The aim of this study was to report the long‐term outcomes in patients with multiple myeloma (MM) who receive dialysis treatment for acute kidney injury (AKI) due to myeloma cast nephropathy and subsequently recover renal function. Methods: Patients presenting with dialysis‐dependent AKI secondary to myeloma cast nephropathy and subsequently recovering independent renal function between January 2005 and December 2012 were included in this study. Both renal and haematological parameters were collected at multiple time points as part of routine clinic practice. Factors associated with renal function and overall survival (OS) were determined. Results: Twenty‐four patients fulfilled the criteria for inclusion. Mean age was 62.1 years; 75% were male and 75% were of White ethnicity. The median OS was 64.1 months (95% confidence interval [CI] 34.8–93.3). Twenty‐three (95.8%) patients remained dialysis‐independent until death or end of follow‐up; one patient required further haemodialysis treatment during the follow‐up period. The independent determinant of worse OS was a known history of chronic kidney disease (CKD) at presentation. Shorter length of time on haemodialysis and higher percentage reduction in clonal serum FLC at day 21 from baseline predicted better excretory renal function (estimated glomerular filtration rate) at 6 months. Conclusion: In this series, the large majority of patients with MM and dialysis‐dependent AKI secondary to myeloma cast nephropathy who recovered independent renal function had no requirement for further dialysis. Survival following recovery of renal function is good, and early variables are independently associated with survival and future renal function.